The influence of security, word of mouth, experience and information to brand trust on internet banking website - MELISSA JANNY JEANETTE DUMANAUW; WIBISONO SOEDIONO (Jurnal Bisnis dan Akuntansi, 2015)
The purpose of this study is to investigate the influence of security, experience, and information to brand trust on internet banking website. Data for this study was obtained from 100 respondents who become user customer of Internet Banking and who has experience of doing transaction through Internet Banking for at least more than 1 year. The data was collected by spreading the questionnaire as the instrument. The data used in this research are convenience sampling. This research examines how brand trust is affected by the security, good online experience, and quality of information.The research finding can be summarized as follows. Security, Experience, and Information all significantly influence brand trust on Internet Banking.